PATOGENESITAS Streptococcus agalactiae DAN Streptococcus iniae PADA IKAN NILA (Oreochromis niloticus) - Dudung Daenuri; Walson Halomoan Sinaga (Research Center for Biology-Indonesian Institute of Sciences, 2011)
The objectives of this study are to test the pathogenicity of Streptococcus agalactiae and Streptococcus iniae in Nile Tilapia(Oreochromis niloticus) A challenge test was carried out in the Laboratory of Semarang Fish Quarantine. The method used in this study was the Completely Randomize Design(CRD) with three bacterial treatments Streptococcus agalactiae, Streptococcus iniae and control, three dose 107 ,108 , 109 with three replications for each treatment. The observed parameters include identification and reisolation of Streptococcus agalactiae, Postulat Koch test, survival rate (SR), and clinical symptoms. The result of this research showed that the survival rate of Nile Tilapia which has challenged by Streptococcus agalactiae was lower than that of Nile Tilapia which has challenged by Streptococcus iniae.